Components Analysis of Metabolic Syndrome in Acute Myocardial Infarction Patients - MMR, Khan; NK, Sana; Basak, PM; Sarker, BC; Islam, M Akhtarul; Jahan, KI; Rahman, MK; Rashid, MHO; Sarker, A; Das, CK; et al. (TAJ: Journal of Teachers Association, 2018)
Background: Metabolic syndrome confers the risk of developing acute myocardial infarction which is the most common form of coronary heart disease and the single most important cause of premature death worldwide. The frequency and association of different components of metabolic syndrome on AMI are not well understood and has not been well evaluated. Objective: The aim of this study was to assess the components of the metabolic syndrome and its association with AMI patients. This study will help in awareness building in reducing AMI by early detection of components of metabolic syndrome. Patients and methods: This was a prospective observational study consisted of 325 AMI patients who were aged >20 years. Patients with first time AMI arriving in CCU of Rajshahi medical college during the period of 2012-2014, were included. Data were collected through interview, clinical examination, and laboratory tests within 24 hrs of AMI. Five components of metabolic syndrome were defined according to criteria set by modified NCEP ATP III (according to ethnic variation). Results: In AMI patients (n=325), no metabolic components were in 24 (7.4%) patients, one in 53 (16.3%), 2 components in 91(28.0%), 3 components were in 61(18.8%), 4 in 67(20.6%) and all 5 components were in 29 (8.9%) patients. In this study, there was no component in 7.4% of AMI patients, at least 1 component was 92.6%, at least 2 components were 76.3%, at least 3 components were 48.3%, at least 4 components were 29.5% and at least 5 components were 8.9%. The Metabolic syndrome was 48.3% (n=157). Among metabolic syndrome (≥3 components) in AMI (n=157, 48.3%) 4 components (20.6%) were more, next was 3 components (18.8%) and than 5 components (8.9%). Overall frequencies of components in acute myocardial infarction (n=325) were in order of abdominal obesity (54.8%) > high blood pressure (54.5%) > high FPG (54.2%) > Triglyceride (46.2%) and low HDL-C (46.2%) in acute myocardial infarction. Highest percentage was observed in abdominal obesity (54.8%) followed by high blood pressure (54.5%) and FPG (54.2%). TAJ 2016; 29(2): 6-10